A Quasi-Experimental Study on the Effectiveness of Activity Worksheets in Enhancing Grade 9 Learners’ Performance in Geometry - Algyr Cabanillas (Research Synergy Foundation, 2026)
This quasi-experimental research design determined the effectiveness of the activity worksheets in enhancing the academic performance of Grade 9 learners in Mathematics. Match-pairing sampling technique was used in this study. Weighted mean and standard deviation were used to determine the learners’ performance in Mathematics. The t-test was used to determine whether there was a significant difference or increase in the study's findings. On the other hand, the difference between pre-test and post-test mean scores of the same individual or observation was measured using the t-test for paired samples and Cohen's d to determine the effect size. Based on the findings the researcher concluded that there is no significant difference between the two groups' mean scores on formative tests and post-test. More so, the test of mean scores of the students in each group found that there is a significant difference between the experimental group's pre-test and post-test mean scores, but no significant difference between the pre-test and post-test means scores of the comparison group. The researcher recommended that the continuation of the Activity Worksheets in Mathematics as part of the school’s intervention.